Retrospective analysis of clinical characteristics and treatment of children and adolescents with depression - Jiang, Xiaolu; Zheng, Hongyu; Yang, Rong; Wang, Shuo; Zhong, Hui (Frontiers in Psychiatry, 2023)
The purpose of this study was to analyze the demographics, clinical characteristics, and treatment of depression in children and adolescents in different age groups. A total of 635 cases of children and adolescents with depression in a hospital were collected through electronic records from January 2014 to December 2021. They were grouped according to the age of onset, amounting to 115 cases in childhood (8–12), 359 early adolescents (13–15), and 161 cases in late adolescence (16–18). The three groups were compared in terms of general conditions, clinical characteristics, and treatment. Results showed that over the past 8 years, the proportion of hospitalizations in the early adolescence group has been increasing, that in the late adolescence group was lower than that in previous years, and gender (X2 = 16.66, P < 0.001), psychotic symptoms (X2 = 6.224, P = 0.045), and disease course (Z = 84.617, P < 0.001) were significantly different. No significant differences were found in drug treatment regimen, suicide, length of hospital stay, or family history among the three groups. There were differences in the general conditions and clinical characteristics of children and adolescents with depression at different onset ages. The number of hospitalized children and adolescents with depression is increasing annually, and the proportion of hospitalizations in the children group was higher than that in previous years. Females are more likely to suffer from the disease and present more psychotic symptoms. The course of the disease in the early adolescence group was shorter than that in the other two groups, and the late adolescence group had more males and fewer psychotic symptoms.